Пошаговое объяснение:
при у=3 5+4*3=5+12=17
при у=-7 5+4*(-7)=5-28=-23
при у=0,25 5+4*0,25=5+1=6
при у =- 4/3 5+4*(-4/3)=5-5 1/3=-1/3
при у=-1/42 5+4*(-1/42)=5-2/21=4 19/21
5+4y
1) 5+4*3 = 5+12 = 17
2) 5+4*(-7) = 5+(-28) = -23
3) 5+4*0,25 = 5+1 = 6
4)
5) 5+4* = 5+ = 5+(-) =
Пошаговое объяснение:
при у=3 5+4*3=5+12=17
при у=-7 5+4*(-7)=5-28=-23
при у=0,25 5+4*0,25=5+1=6
при у =- 4/3 5+4*(-4/3)=5-5 1/3=-1/3
при у=-1/42 5+4*(-1/42)=5-2/21=4 19/21
5+4y
1) 5+4*3 = 5+12 = 17
2) 5+4*(-7) = 5+(-28) = -23
3) 5+4*0,25 = 5+1 = 6
4)![5+4*(-\frac{4}{3}) = 5+\frac{4}{1} * \frac{4}{3} = \frac{16}{3} = (-5\frac{1}{3}) = 5-5\frac{1}{3} = -\frac{1}{3}](/tpl/images/0962/7739/ee3ec.png)
5) 5+4*
= 5+
= 5+(-
) = ![5 + (-\frac{2}{21}) = 4\frac{21}{21} + (-\frac{2}{21}) = 4\frac{19}{21}](/tpl/images/0962/7739/c11b6.png)